2017
DOI: 10.1093/ije/dyx070
|View full text |Cite
|
Sign up to set email alerts
|

Does unmeasured confounding influence associations between the retail food environment and body mass index over time? The Coronary Artery Risk Development in Young Adults (CARDIA) study

Abstract: Longitudinal associations between neighbourhood food outlets and BMI were greater in magnitude using a causal model, suggesting that weak findings in the literature may be due to residual confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the three continuous food swamp measures we used, which were based on previous studies utilizing relative food environment measures [ 23 , 30 , 33 , 34 , 39 , 47 ]. All county-level food store data was sourced from the Food Environment Atlas.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…We test the effect of food access on obesity rates by using a county-level unit of analysis [ 26 ]. This approach complements the current literature as it is more aggregated than the local community level [ 27 , 28 , 29 , 30 , 31 , 34 , 35 , 39 ], but less aggregated than the state level [ 32 , 42 ]. Previous work by Dunn [ 26 ] and Blanchard and Lyson [ 43 ] documents significant county-level variations in access to fast food restaurants or grocery stores.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations